PENGARUH KUALITAS PRODUK, HARGA, KEMASAN, DAN DIGITAL MARKETING TERHADAP LOYALITAS PELANGGAN MS GLOW SKINCARE DI KECAMATAN WANGON - Jayanti, Esih; Fiannanda, Rismaya; Sugiharto, Irwan Saputro (JURNAL EKONOMI, 2024)
This study aims to examine the effect of Product Quality (X1), Price (X2), Packaging (X3), and Digital Marketing (X4) on Customer Loyalty (Y) of Ms Glow's skincare in Wangon District. The sampling technique in this study used non-probability sampling with a sample of 100 respondents. The data collection technique was carried out by distributing questionnaires via Google Forms. Analysis prerequisite tests include normality, linearity, multicollinearity, and heteroscedasticity tests. Data analysis technique using multiple linear regression. Statistical tests through the T, F, R square test (R2), and the classical assumption tests. The results showed that: (1) Product quality had an effect on Ms Glow skincare customer loyalty, (2) Prices had an effect on Ms Glow skincarecustomer loyalty, (3) Packaging had no effect on Ms Glow skincare customer loyalty, (4) Digital marketing had no effect on Ms Glow skincare customer loyalty, (5) Product quality, price, packaging, and digital marketing simultaneously affect customer loyalty.